Impact of The Fitness Competition Preparation on Stress Biomarkers and Sleep - Mbay, Theo (2020)
The lack of adequate energy may act as a threat to homeostasis and thus result in the activation of the neuroendocrine system. There is evidence that dietary restraint is physiologically stressful, however, the data on fitness competition preparation is more mixed. Thus, the aim of this thesis was to investigate the impact of fitness competition preparation on serum cortisol and heart rate variability as stress biomarkers as well as the effects on sleep quality. The study used a longitudinal design. The participants were eight male fitness athletes (31  5 years old) with 11  8 years of resistance training experience. Emfit QS was used to record nocturnal heart rate variability (HRV) and heart rate (HR) as well as bed and sleep times every night over the study period. Data from before (PRE), at the start (START), at mid-point (MID) and at the end of the competition preparation (END) were analysed. On average, START, MID and END correspond to 19 ± 4, 10 ± 2 and 2 ± 2 weeks before the competition, respectively. Total body mass, fat mass and lean mass (Dual-energy X-ray absorptiometry) and basal serum cortisol concentrations were assessed at PRE and END and basal serum cortisol concentrations were assessed at PRE and END. Energy availability decreased (38 ± 3 vs. 18 ± 4 kcal/kg/FFM) while energy expenditure increased (24 ± 4 vs. 44 ± 15, met/h/week from PRE to END. Body mass (from 89.4 ± 12.8 kg to 77.9 ± 6.0 kg) and fat mass (14.9 ± 6.5 kg vs 4.7 ±1.7 kg) decreased from PRE to END. Nocturnal HRV increased from PRE (60 ± 14 ms) to END (69 ± 19 ms) and was strongly associated with the change in fat mass (r= 0.90, p<0.01). There was a nonsignificant increase in serum cortisol from PRE to END (357 ± 102 nmol/l vs 402 + 76 nmol/l). Nocturnal HR decreased from PRE to END (57 ± 2 bpm vs. 50 ± 4 bpm) and was associated with overall energy intake (r= 0.68). Sleep disturbances were not observed during the study period, in fact, sleep time increased by 36 ± 19 min from START to end (7h 36 ± 34 min vs 8h 12 ± 41 min). The main finding of the study was that HRV increases in response to prolonged energy restriction and weight loss among normal-weight individuals. These findings are in accordance with the concept of adaptive thermogenesis. The increase in serum cortisol, although non-significant, highlights the physiological stress of energy restriction. Finally, sleep quantity appears to be maintained during prolonged energy restriction, however, possible changes in sleep architecture require more investigation.